Laryngeal and hypopharyngeal cancers and occupational exposure to formaldehyde and various dusts: a case-control study in France. Issue 11 (1st November 2000) - Laforest, Laurent; Luce, Danièle; Goldberg, Paquerette; Bégin, Denis; Gérin, Michel; Demers, Paul A; Brugère, Jacques; Leclerc, Annette
Abstract : OBJECTIVES: A case-control study was conducted in France to assess possible associations between occupational exposures and squamous cell carcinomas of the larynx and hypopharynx. METHODS: The study was restricted to men, and included 201 hypopharyngeal cancers, 296 laryngeal cancers, and 296 controls (patients with other tumour sites). Detailed information on smoking, alcohol consumption, and lifetime occupational history was collected. Occupational exposure to seven substances (formaldehyde, leather dust, wood dust, flour dust, coal dust, silica dust, and textile dust) was assessed with a job exposure matrix. Exposure variables used in the analysis were probability, duration, and cumulative level of exposure. Odds ratios (ORs) with their 95% confidence intervals (95% CIs) were estimated by unconditional logistic regression, and were adjusted for major confounding factors (age, smoking, alcohol, and when relevant other occupational exposures). RESULTS: Hypopharyngeal cancer was found to be associated with exposure to coal dust (OR 2.31, 95% CI 1.21 to 4.40), with a significant rise in risk with probability (p<0.005 for trend) and level (p<0.007 for trend) of exposure. Exposure to coal dust was also associated with an increased risk of laryngeal cancer (OR 1.67, 95% CI 0.92 to 3.02), but no dose-response pattern was found. A significant relation, limited to hypopharyngeal cancer, was found with the probability of exposure to formaldehyde (p<0.005 for trend), with a fourfold risk for the highest category (OR 3.78, 95% CI 1.50 to 9.49). When subjects exposed to formaldehyde with a low probability were excluded, the risk also increased with duration (p<0.04) and cumulative level of exposure (p<0.14). No significant association was found for any other substance. CONCLUSION: These results indicate that exposure to formaldehyde and coal dust may increase the risk of hypopharyngeal cancer.